Spillover Analysis of Carbon Market, Crude Oil Market, and Coal Market based on BEKK-GARCH - Zhang, Xinyuan (Transactions on Economics, Business and Management Research, 2024)
Global warming has become an urgent issue for all mankind, and climate change caused by carbon dioxide emissions is a growing concern. China, as a major global energy consumer, has set "carbon neutrality" as its vision for 2035. This study aims to explore the impact of carbon neutral policy on the volatility of the energy market, and through a comprehensive analysis of the historical data of the carbon market, crude oil market, and power coal market returns, we aim to reveal the volatility spillover effect among markets. In this study, we determine the distribution trend of yield receipts as t-distribution by performing statistical tests, ADF analysis on the yield historical data of the three markets. Under this premise, ARCH model, GARCH model and EGARCH model are further used to carry out the preliminary validation of the yield series of each market, and under the premise of ensuring the existence of volatility benefits in the data of each market, BEKK-GARCH model is used to carry out the analysis of multi-market spillover benefits, and the significance of the results is ensured by the WALD test. Finally, the results of the study are linked to actual policies and market operations to provide relevant recommendations for governments, investors, enterprises and carbon trading platforms. This study provides in-depth market perspectives and policy support for addressing the challenge of climate warming, and provides strong data support and decision-making reference for achieving the goal of carbon neutrality.